PUBLIC SMOKING ISSUE - JANUARY 1986 REPORT (Tufts Archival Research Center, 2007)
CONFIDENTIAL; Memorandum from Susan Stuntz, Jeff Ross, and Lisa Osborne to Peter Sparber regarding the 1986 report on public smoking. Discusses efforts to build on coalition work done in relation to workplace smoking policy implementation. Highlights the use of workplace smoking kits and follow-up studies done on their success rates. Mentions the role of organized labor around the issue of workplace smoking.